2017
DOI: 10.2116/analsci.33.839
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electron Transfer-type Bioelectrocatalysis of Peroxidase at Mesoporous Carbon Electrodes and Its Application for Glucose Determination Based on Bienzyme System

Abstract: Non-catalytic direct electron transfer (DET) signal of Compound I of horseradish peroxidase (POD) was first detected at 0.7 V on POD/carbon nanotube mixture-modified electrodes. Excellent performance of DET-type bioelectrocatalysis was achieved with POD immobilized with glutaraldehyde on Ketjen Black (KB)-modified electrodes for H2O2 reduction with an onset potential of 0.65 V (vs. Ag | AgCl | sat. KCl) without any electrode surface modification. The POD-immobilized KB electrode was found to be suitable for de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 34 publications
4
20
0
Order By: Relevance
“…To obtain an efficient direct electron transfer, the orientation of BOD needs to be controlled in such a way that the active center T1 is close to the electrode surface . In the last decades, numerous strategies have been proposed to immobilize BOD on various electrodes allowing efficient DET . To name a few, DET was achieved by BOD adsorption on electrodes functionalized with carboxyl groups, or by pulse‐assisted techniques .…”
Section: Introductionmentioning
confidence: 99%
“…To obtain an efficient direct electron transfer, the orientation of BOD needs to be controlled in such a way that the active center T1 is close to the electrode surface . In the last decades, numerous strategies have been proposed to immobilize BOD on various electrodes allowing efficient DET . To name a few, DET was achieved by BOD adsorption on electrodes functionalized with carboxyl groups, or by pulse‐assisted techniques .…”
Section: Introductionmentioning
confidence: 99%
“…A 20-μL aliquot of a 12 mg mL -1 POD solution dissolved in 0.1 M phosphate buffer (pH 7.0) containing 5% glutaraldehyde (GA) as a cross-linker reagent was applied on the aforementioned electrode surface and placed in a water-saturated atmosphere for 2 h at 4 C. GA was reported to improve the DET-type catalytic current density and stability of POD on mesoporous carbon electrodes. 51 The enzyme-modified electrodes were washed with a buffer solution before electrochemical measurements.…”
Section: Electrode Preparationmentioning
confidence: 99%
“…[46][47][48][49][50] However, it has recently been reported that POD can work as a DET-type biocatalyst at suitable mesoporous electrodes to reduce H2O2 at a potential close to the redox potential of the protoheme (Compound I) of POD (0.7 V vs. Ag/AgCl at pH 7). [51][52][53] Such DET-type reactions of POD will draw attention of constructing bienzyme-type biosensors without any mediator. For practical purposes, it is important to easily construct scaffolds for DETtype enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical methods based on nanomaterial modified electrodes, due to their high electrical and optical properties, have attracted attention concerning measurements of biomolecules and drugs over the past decade. [29][30][31][32] CNTs have become preferred in most cases because of their high conductivity and chemical properties, 1 thus, CNTs can greatly improve the sensitivity of the electrochemical measurements and minimize the detection limit. However, due to the strong vander Waals force between CNTs, the dispersion is very poor in most solvents, and its huge surface area and graphene sheet structure determine that its enrichment effect on many analytes having poor selectivity.…”
Section: Introductionmentioning
confidence: 99%